2005
DOI: 10.1074/jbc.m412222200
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Target Enzyme Recognition of the β-Trefoil Fold Barley α-Amylase/Subtilisin Inhibitor

Abstract: The barley ␣-amylase/subtilisin inhibitor (BASI) inhibits ␣-amylase 2 (AMY2) with subnanomolar affinity. The contribution of selected side chains of BASI to this high affinity is discerned in this study, and binding to other targets is investigated. Seven BASI residues along the AMY2-BASI interface and four residues in the putative protease-binding loop on the opposite side of the inhibitor were mutated. A total of 15 variants were compared with the wild type by monitoring the ␣-amylase and protease inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The latter residue has a functional role in the inhibition of barley α-amylase as shown using the BASI mutants E168Q and E168T. 33 …”
Section: ■ Resultsmentioning
confidence: 99%
“…The latter residue has a functional role in the inhibition of barley α-amylase as shown using the BASI mutants E168Q and E168T. 33 …”
Section: ■ Resultsmentioning
confidence: 99%
“…The BASI-AMY2 complex has been well described using site-directed mutagenesis, crystallography, surface plasmon resonance, and activity inhibition analyses (Vallée et al 1998;Rodenburg et al 2000;Nielsen et al 2003;Bønsager et al 2005) and found to have high stability, sub-nanomolar affinity; specific residues were assigned functional roles both in enzyme and inhibitor for the complex formation. Analysis of the LDI-limit dextrinase complex is just initiated thanks to breakthroughs with successful heterologous production of both LDI and limit dextrinase (M. VesterChristensen et al, manuscript in preparation) and data now emerge showing sub-nanomolar affinity also for this complex (J.M.…”
Section: New Roles and Diversity Of α-Glucan-active Enzymes In Biologmentioning
confidence: 99%
“…CM16, CMb (identified in barley and spelt) and CM3 and CM1 (discovered in durum) belong to "CM-proteins". Wheat α-amylase/subtilisin inhibitor (WASI; detected in spelt) inactivates alphaamylase from animal and insect origin and it is also able to inhibit subtilisin (Bønsager et al 2005). CM proteins as well as WASI are connected with IgE wheat allergy (Sotkovsky et al 2011).…”
Section: Discussionmentioning
confidence: 99%